Club Convergence dalam Paradigma Kemiskinan di Indonesia Tahun 2007 - 2022 - Syahadati, Amelia; Hartania, Made Sukma (Seminar Nasional Official Statistics, 2024)
Following the objectives of the Sustainable Development Goals (SDGs), poverty alleviation requires a trend of national poverty convergence to zero. This study aims to look at the convergence pattern of poverty in Indonesia's provinces and the factors that influence it. The research results show that there is no absolute convergence in grouping according to the percentage of poor people, the depth and severity of poverty index and the tendency towards club convergence. The data processing results related to the formation of group convergence noted the formation of seven groups for the percentage of poor people and the poverty depth index and two groups for the poverty severity index. Testing the ordered logit model for each group shows the significance of the influence of the initial and previous conditions of the Gini ratio, per capita expenditure and minimum cost for eliminating poverty on the formation of each convergence group.